STRUKTUR KECEPATAN GELOMBANG S DI BAWAH INDONESIA MELALUI ANALISIS SEISMOGRAM GEMPA-GEMPA BUMI DI SEKITAR INDONESIA PADA STASIUN OBSERVASI UGM - Santosa, Bagus Jaya (UI Scholars Hub, 2008)
Seismogram Analysis of Earthquakes Around Indonesia In UGM Observational Station: S Velocity Structure. The seismogram comparison between the measured and synthetics seismogram has been carried out in observation station of UGM, where the seismograms are excited by earthquakes that occurred at North Sumatra, Sumbawa, Sunda Strait, around North Celebes and PNG. The ray paths from earthquake's hypocenter to UGM give opportunity to understand the earth structure alongside the front area of subduction zone. The calculation of synthetic seismogram needs input in the form of earth model, the Centroid Moment Tensor (CMT) solution of the earthquake and location of observation station, as well as the relevant date file response of the observation station. Waveform comparison and fitting at surface wave indicate that speed's anomalies in the lithosphere have negative character in front area of subducted zone, but become positive for northern area of subduction zone. By paying attention to waveform of Love surface wave, it is obtained, that this waveform are sensitive to the change of earth crust thickness, while Rayleigh waveform is not sensitive. Heterogeneity is not only occurred in the lithosphere, but also in deeper earth layers, until Core Mantle Boundary (CMB). Different corrections are needed to make the fitting at S secondary wave, but also at depth wave and its repetitions. The result of this research shows that the research area, which is located in the front of subduction zone has anomalies at S speed of at deeper earth layers which than the lithosphere. The earth structure as the result of this research differs from the other seismological results, where they used the methods, which are based on inversion of arrival time data of body wave and dispersion analysis on surface wave.